The Effect of Audit Tenure, Workload, and Company Size on Audit Quality - Agustianto, Divo Ridho; Zakaria, Adam; Respati, Dwi Kismayanti (Jurnal Akuntansi, Perpajakan dan Auditing, 2022)
This study aims to determine the effect of audit tenure, workload, and firm size on audit quality. This study uses secondary data. The purposive sampling method was used as a sampling technique with 53 selected companies from all infrastructure, utilities, and transportation companies listed on the Indonesia Stock Exchange in 2018-2020. The data were processed by multiple linear regression and SPSS 25.0 program. The results of this study indicate that workload and firm size have a positive effect on audit quality. Meanwhile, audit tenure has no effect on audit quality.